2008
DOI: 10.1165/rcmb.2007-0224rc
|View full text |Cite
|
Sign up to set email alerts
|

The Prolonged Life-Span of Alveolar Macrophages

Abstract: To further examine the half-life of alveolar macrophages, chimeric CD 45.2 mice were generated through bone marrow transplantation of donor CD 45.1 cells. Before administration of donor cells, recipient mice were divided into two cohorts: the first cohort received total body irradiation; the second cohort also received irradiationhowever, the thorax, head, and upper extremities were shielded with lead. Flow cytometric analysis was then performed on blood, peritoneal, and bronchoalveolar lavage cells over time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 19 publications
7
124
0
Order By: Relevance
“…Importantly, the Mreg characterized in our studies efficiently interferes with distinct inflammatory reactions after adoptive transfer and induces the production of IL-10 by CD4 + T cells in vivo, as well as in cultures of Ag-specific stimulated CD4 + T in vitro. Our findings are in line with several studies that demonstrate the longevity of macrophages and their immunosuppressive potential (22,23,41,42). Yet, to our knowledge, this is the first study to characterize a macrophage population induced by a single pathogen-derived immunomodulator that exerts immunosuppressive activities in unrelated inflammatory settings.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, the Mreg characterized in our studies efficiently interferes with distinct inflammatory reactions after adoptive transfer and induces the production of IL-10 by CD4 + T cells in vivo, as well as in cultures of Ag-specific stimulated CD4 + T in vitro. Our findings are in line with several studies that demonstrate the longevity of macrophages and their immunosuppressive potential (22,23,41,42). Yet, to our knowledge, this is the first study to characterize a macrophage population induced by a single pathogen-derived immunomodulator that exerts immunosuppressive activities in unrelated inflammatory settings.…”
Section: Discussionsupporting
confidence: 92%
“…Other investigators have observed this result using radiation-limited bone marrow transplantation techniques that are complementary to ours (26)(27)(28). However, an inherent problem with bone marrow transplant techniques is that local replication cannot be excluded as a source for macrophage replacement.…”
Section: Discussionmentioning
confidence: 69%
“…Alveolar macrophages are very long-lived cells that may live for very prolonged periods in the steady state [10]. In murine models there was no detectable turnover and little local replication observed over 8 months, so in a steady state there may be only a limited requirement for in-situ replication because of intrinsic macrophage persistence.…”
Section: Macrophage Adaptation To Functionmentioning
confidence: 99%